2009
DOI: 10.1007/s10750-009-9934-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of external perturbations on the functional composition of phytoplankton in a Mediterranean reservoir

Abstract: The changes in abundance and composition experienced by phytoplankton communities in lakes and reservoirs occur in response to variations in the physical (light climate or energy) and the chemical (nutrient availability or resources) constraints for algal growth. Mediterranean reservoirs are very dynamic systems, subject to frequent changes in the physical environment as a result of water management operations, which suggests that phytoplankton communities might also undergo frequent changes. The phytoplankton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 62 publications
2
26
0
2
Order By: Relevance
“…Therefore, reservoir outflow during the FHIP was not sufficient to cause significant phytoplankton community changes, as compared to the normal hydrocondition observed in Cruzeta reservoir (Chellappa et al, 2008) and in ARG reservoir (Chellappa et al, 2009) of Rio Grande do Norte. The results of similar nature have been described at El Gerdal Reservoir in the southwest of Spain (Hoyer et al, 2009). The present study indicates the cyanobacterial species dominance immediately after a long period without water renewal and phytoplankton community changes affecting diversity when an external disturbance occurred.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, reservoir outflow during the FHIP was not sufficient to cause significant phytoplankton community changes, as compared to the normal hydrocondition observed in Cruzeta reservoir (Chellappa et al, 2008) and in ARG reservoir (Chellappa et al, 2009) of Rio Grande do Norte. The results of similar nature have been described at El Gerdal Reservoir in the southwest of Spain (Hoyer et al, 2009). The present study indicates the cyanobacterial species dominance immediately after a long period without water renewal and phytoplankton community changes affecting diversity when an external disturbance occurred.…”
Section: Discussionsupporting
confidence: 87%
“…These scenarios are induced by strong seasonal winds and water removal operations in reservoirs that lead to a variety of sudden and unexpected changes in the phytoplankton community. These auto and allogenic factors may induce thermal structure changes in the water column and control the composition, biovolume and functional diversity the phytoplankton community (Hoyer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the studied period, the breaking down of the thermocline was followed by a consistent increase in z mix /z eu . The effects of z mix /z eu ratio on phytoplankton assemblages were reported in Mediterranean region (Naselli-Flores and Barone, 1998, 2000Naselli-Flores, 2000;Hoyer et al, 2009;Becker et al, 2010). The ratio is a good descriptor of the underwater light climate experienced by phytoplankton and its values can be related to the morphological structure of phytoplankton assemblage, Tug˘ba Ongun Sevindik et al: Ann.…”
Section: Biomassmentioning
confidence: 95%
“…The habitat template for this group has been described as mesotrophic, small-and medium-sized lakes (Reynolds et al 2002, Padisák et al 2009), which corresponds with the characteristics of the Pareja limno-reservoir (Molina-Navarro et al 2012). Group B has also been described as dominant in other Spanish reservoirs, but only during the mixing period (Moreno-Ostos et al 2008, Hoyer et al 2009). As a consequence of thermal stratification, nonbuoyant and nonmotile phytoplankton species such as group B diatoms are thought to sink into the hypolimnion (Hoyer et al 2009); however, functional group B showed a high percentage of the total biovolume in the Pareja limno-reservoir in spring and summer, especially in the dam zone (Table 4).…”
Section: Phytoplankton Compositionmentioning
confidence: 99%
“…The functional group approach has been successfully applied in Mediterranean lakes and reservoirs (e.g., Moustaka-Gouni et al 2007, Katsiapi et al 2011, although the number of Mediterranean applications is limited. In the Iberian Peninsula, some studies have been conducted in the Tablas de Daimiel and Xeresa wetlands (Lionard et al 2005, Romo andVillena 2005), in the El Gergal Reservoir (Hoyer et al 2009), and in the Sau Reservoir (Becker et al 2010); however, these study areas are all quite different from the Pareja limno-reservoir.…”
mentioning
confidence: 99%